Islamic theology and sustainable peace: the case of Darunnajah Islamic Boarding School - Darojat, Much Hasan; Izfanna, Duna; Artalim Zaim, Muntaha; Ogunbado, Ahamad Faoisy (UIN Fatmawati Sukarno Bengkulu, 2025)
This article aims to explore the role of Darunnajah Islamic Boarding School in building sustainable peace based on Islamic theology. The theological approach chosen is Ahlusunnah wal Jamaah in Asy‘ariyyah formulation. This belief applies a moderate attitude and keeps people away from judgmental or disbelieving attitudes. This research uses a qualitative approach, combining interviews and document analysis of Darunnajah’s peace education programs, including international language and cultural collaborations and data from official reports and the institution’s website. Theological concepts are analyzed using authoritative primary and secondary references to explain how Pesantren, as an Islamic educational institution, integrates Islamic values with local wisdom to shape students’ character and promote peace. The results show that Darunnajah applies a holistic approach involving character education, foreign language skills, and classical Arabic book literacy. It also fosters awareness of global peace and cross-cultural understanding while maintaining Islamic identity. This study concludes that Darunnajah’s integration of Islamic theology as the foundation of peace education can serve as a model for sustainable peacebuilding.